The Cardiovascular Factors and Metabolic Syndrome in an Elderly Male Chinese Occupational Population - Pei-En Chen; Hsi-Che Shen; Yi-Chun Hu; Yu-Fen Chen; Tao-Hsin Tung (Journal of Men's Health, 2019)
Purpose